Aktivitas Antioksidan dan Inhibitor Enzim Tirosinase Ekstrak Daun Pepaya (Carica papaya L.) - Yohana Simamora; Edy Fachrial; Hariyadi Dharmawan Syahputra (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Skin aging and hyperpigmentation are closely related to increased oxidative stress and tyrosinase enzyme activity in the melanogenesis process. Utilization of natural ingredients that have antioxidant activity and the ability to inhibit tyrosinase is one potential approach in skin care. This study aims to evaluate the antioxidant activity and the potential for inhibiting the tyrosinase enzyme from ethanol extract of papaya leaves (Carica papaya L.). The study was conducted experimentally through the stages of simplicia preparation, extraction using the ultrasonication method, phytochemical screening, antioxidant activity testing using the DPPH method, and tyrosinase inhibition test using L-DOPA and kojic acid as a positive control substrate. The results of the phytochemical screening showed that the ethanol extract of papaya leaves contained flavonoids, alkaloids, tannins, and triterpenoids, while saponins were not detected. Antioxidant activity testing showed an increase in free radical inhibition ability along with increasing extract concentration. In addition, the results of the tyrosinase enzyme inhibition test showed that papaya leaf extract was able to significantly suppress enzyme activity. Based on these results, papaya leaf ethanol extract has the potential to be developed as a source of natural antioxidants and a tyrosinase enzyme inhibitor agent.